Principles of transportation economics - Boyer, Kenneth Duncan (Addison-Wesley series in economics, 1997)
Principles of Transportation Economics is an introduction into the distinctive elements of transportation economics, describing how the standard pieces of economic analysis are applied in the transport sector. Boyer's text reflects transportation economics as it is taught and practiced today. Unlike its many predecessors, its arguments do not discuss the practice of economic regulation. Legal issues and concerns of regulatory process are no longer a central part of transportation economics, and this book reflects this shift. The analysis covers the modern developments of subsidy-free pricing and stand-alone costing - See more at: http://www.pearsonhighered.com/educator/product/Principles-of-Transportation-Economics/9780321011039.page#sthash.YZbLtgwH.dpuf